Length-weight relationship, relative condition factor and fecundity of Notopterus notopterus (Pallas, 1769) from river Brahmaputra in Dhubri, Assam, India - Paul, Mitali Ghosh; Priyam Nath; Amalesh Dutta (Journal of Fisheries, 2022)
Notopterus notopterus (Pallas, 1769) commonly known as bronze featherback is an important freshwater fish widely distributed in deep and clean waters in the rivers, beels, reservoirs and ponds. This study elucidates the length-weight relationship (LWR), relative condition factor and fecundity of N. notopterus collected from the river Brahmaputra in Dhubri, Assam, India. A total of 181 fish specimen were sampled. The LWR showed a positive isometric growth with uniform increase in height or width with increasing length. The value of a and b in males were 0.0120 and 3.06 respectively. In females, a and b were slightly higher being 0.0230 and 3.18 respectively. The coefficient of determination for combined sex was equal to 0.8572 (p < 0.001). The relationship between the fecundity and four variables viz. total length, body weight, gonadal length, gonadal weight were analysed and the relationship between the fecundity and gonad weight was much more significant than other variables considered. The current study might serve as a valuable guideline for establishing future biometric studies for fishes collected from this stretch of the river Brahmaputra.